Agile Strategies in Software Project Management and Traditional Management Approaches (Contemporary Journal of Social Science Review, 2024)
Over the past few decades, the significance of knowledge work has caused companies to shift from a progressive way of dealing with project management to a more cooperative working style. A flexible project management system is essential for project managers in today's increasingly interconnected world, where they must respond quickly and effectively to new threats and opportunities. "Agile" project management practices are well-versed in the necessity of distributing responsibility and initiative in support of transformation to change. In this article, we will compare and contrast Agile Project Management with more conventional methods of project management, focusing on its past practices and current applicability. Considering the increased complexity and unpredictability of projects in the modern economy, Agile Project Management has emerged as a useful tool for both the modern knowledge worker and the project managers responsible for their execution. Aiming to promote the adoption of the agile approach in the business world, this document provides an overview of the framework.